(E)-2-Styrylanthracene-9, 10-dione: A new type of fluorescent probe core and its application in specific mitochondria imaging. (December 2021) - Zhang, Xu; Zhang, Ting-jian; Wang, Zhao-ran; Wang, Qiu-yin; Lu, Peng-fei; Zhao, Hai-yang; Wang, Lin; Meng, Fan-hao
Abstract: Herein, a new type of fluorescent probe core, ( E )-2-styrylanthracene-9, 10-dione (EK01 ), was developed which displayed strong fluorescence quantum yield (Φ = 0.867 in DMF; Φ = 0.561 in acetone; Φ = 0.616 in CH2 Cl2 ; Φ = 0.265 in DMSO), good photostability, large stokes shift (90 nm–120 nm) and molar extinction coefficients (0.5875 × 10 4 –0.7609 × 10 4 mol −1 L cm −1 ). During cell assays and co-localization experiments, EK01 showed excellent cell membrane permeability and low cytotoxicity against MCF-10A (human mammary epithelial cell line) and HT-29 (human colorectal adenocarcinoma cell line). Particularly, we surprisingly discovered that EK01 could selectively aggregate in mitochondria and specific stain it in a green emissive fluorescent form, which means that EK01 could be a real-time specifically monitor of mitochondria in living cells with a high signal-to-noise ratio. Hence a new mitochondria imaging method was established which is incubating EK01 with living cells for 1 h at a final concentration of 6–12 μM, then visualizing under a confocal microscope at 395 nm. It is worth noting that the fluorescence efficiency of EK01 is not outstanding in organisms, it has much stronger fluorescence efficiency in other organic solvent systems (such as DMF, acetone and CH2 Cl2 ). Therefore, as a new type of fluorescent core that is easy to synthesis and graft, we believe that ( E )-2-styrylanthracene-9, 10-diones have the potential to develop a variety of fluorescence platforms applying in different fields. Graphical abstract: Image 1 Highlights: A novel fluorescent probe core (EK01 ) was developed for specific mitochondria imaging in living cells. The probe shows massive stokes shift and high fluorescence quantum yield. The probe shows excellent cell membrane permeability and low cytotoxicity. The probe could real-time specifically monitor mitochondria for a long time.